(untitled) (Applied Biological Research, 2019)
The present study was conducted in two consecutive seasons (2014 and 2015) at Agriculture College, Warrangal (India) to assess the combining ability of hybrid rice (Oryza sativa) for various cooking quality parameters. The genotypes involved in the study comprised of 45 F1hybrids generated from 10 parents and two promising check varieties viz., BPT 5204 and Chittimuthyalu. In present study, the magnitude of specific combining ability variances was found higher than general combining ability for all the quality characters studied, except for kernel length, kernel length/breadth ratio and kernel elongation ratio. This indicated the greater role of non-additive gene action in controlling most of these traits. The best specific crosses for cooking quality traits were WGL-32100 x RP-Bio-5478-185 (high x low), Ramappa x RP-Bio-5478-176 (high x low) and Ramappa x RP-Bio-5478 -185 (high x low) and interestingly these crosses involved parent Ramappa. These crosses were highly promising for cooking quality traits.